The immune profile induced is crucial to determine the effects of immunocastration over gonadal function, fertility, and GnRH‐I expression. (19th October 2017) - Siel, Daniela; Loaiza, Alexandra; Vidal, Sonia; Caruffo, Mario; Paredes, Rodolfo; Ramirez, Galia; Lapierre, Lisette; Briceño, Cristóbal; Pérez, Oliver; Sáenz, Leonardo
Abstract : Problem: Immunocastration or vaccination against the GnRH‐I hormone is a promising alternative to reproductive control in different animal species. Given the low immunogenicity of this hormone, the use of adjuvants becomes necessary. Method of Study: This study evaluated the effects of three adjuvants that induce different immune response profiles over gonadal function, fertility, and expression of GnRH‐I. Female mice (n = 6) were vaccinated at days 1 and 30 with a recombinant antigen for immunocastration and different adjuvants that induced preferentially Th1/Th2, Th2, and Th1 immune profiles. Results: Th1/Th2 response is the most efficient to block reproductive activity in vaccinated animals, reducing the number of luteal bodies and pre‐ovulatory follicles. Th2 and Th1/Th2 responses induced an increase in GnRH‐I at the hypothalamus. Conclusion: The immune profile induced by different adjuvants is essential on the effects over fertility, gonadal function, and hypothalamic GnRH‐I expression in immunocastrated animals. Abstract : In female mice vaccinated with a recombinant antigen for immunocastration and different adjuvants that induced preferentially Th1/Th2, Th2, and Th1 immune profiles, the effects of vaccination over gonadal function, fertility, and expression of GnRH‐I were evaluated.